Fully parameterized tube MPC - Raković, S; Kouvaritakis, B; Cannon, M; Panos, C; Findeisen, R (2011)
Reaching a sensible compromise between computational tractability and degree of optimality still remains a significant challenge in robust model predictive control (MPC). Tube MPC offers an efficient approach which is based on pseudo-closed loop optimization but can thus be conservative. The degree of conservatism is reduced through the so-called disturbance affine control policy and it is the aim of this paper to propose a new methodology that deploys a more general policy thereby improving on system theoretic properties yet is no more computationally intensive. The work is based on a suitable parameterization of state and control tubes and is underpinned by guarantees of strong system theoretic properties. © 2011 IFAC.